A critical and comparative study of methods of isolating tumour cells from the blood. Issue 2 (March 1967) - Fleming, J. A.; Stewart, J. W.
Abstract : From the large number of techniques described for isolating tumour cells from the blood, five have been selected because they were those most widely used by previous workers and can be performed with a minimum of special apparatus. These techniques have been assessed for their efficiency in retaining tumour cells added to blood samples, in eliminating normal blood cells, and in preserving the morphology of the retained cells. Those techniques which depend on the differing densities of blood and tumour cells were reliable in recovering tumour cells unaltered morphologically and at the same time eliminating most of the blood cells. Because of its simplicity the silicone flotation technique has been preferred for routine use.